Growth, spectral, optical, laser damage threshold and DFT investigations on 2-amino 4-methyl pyridinium 4-methoxy benzoate (2A4MP4MB): A potential organic third order nonlinear optical material for optoelectronic applications. (May 2018) - Krishnakumar, M.; Karthick, S.; Thirupugalmani, K.; Babu, B.; Vinitha, G.
Graphical abstract: Highlights: 2A4MP4MB exhibits high optical transmittance and thermally stable up to 424 K. The grown 2A4MP4MB exhibits self-defocusing and saturation absorption behavior. Optical limiting properties of 2A4MP4MB have been studied. Large laser damage threshold value of about 3.61 GW/cm 2 has been observed. Abstract: In present investigation, single crystals of organic charge transfer complex, 2-amino-4-methyl pyridinium-4-methoxy benzoate (2A4MP4MB) was grown by controlled slow evaporation solution growth technique using methanol as a solvent at room temperature. Single crystal XRD analysis confirmed the crystal system and lattice parameters of 2A4MP4MB. The crystalline nature, presence of various vibrational modes and other chemical bonds in the compound have been recognized and confirmed by powder X-ray diffraction, FT-IR and FT-Raman spectroscopic techniques respectively. The presence of various proton and carbon positions in title compound was confirmed using 1 H NMR and 13 C NMR spectral studies. The wide optical operating window and cut-off wavelength were identified and band gap value of the title compound was calculated using UV-vis-NIR study. The specific heat capacity (cp ) values of the title compound, 1.712 J g −1 ·K −1 at 300 K and 13.6 J g −1 K −1 at 433 K (melting point) were measured using Modulated Differential Scanning Calorimetric studies (MDSC). From Z-scan study, nonlinear refractive index (n2 ), nonlinear absorption (β) and third order nonlinear susceptibility (χ (3) ) values were determined. The self-defocusing effect and saturable absorption behavior of the material were utilized to exhibit the optical limiting action at λ = 532 nm by employing the same continuous wave (cw) Nd: YAG laser source. The laser damage threshold (LDT) study of title compound was carried out using Nd: YAG laser of 532 nm wavelength. The Vickers' micro hardness test was carried out at room temperature and obtained results were investigated using classical Meyer's law. In addition, DFT calculations were carried out for the first time for this compound. These characterization studies performed on the title compound planned to probe the valuable and safe region of optical, thermal and mechanical properties to improve efficacy of 2A4MP4MB single crystals in optoelectronic device applications.